FEATURES OF MOVEMENTS OF CLIMBING PERCH Anabas testudineus IN WATER FLOW AND ON LAND - Е. D., Pavlov; Tran, Duc Dien; E. V., Ganzha; D. S., Pavlov (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
Climbing perch Anabas testudineus in contradistinction to most fish is able to move not only in water but also on land. In the experiments, we study the diurnal locomotor activity of fish, the features of their movements in flow of clean water and polluted water by urea and thiourea, and the effect of decreasing water level on the crawling and moving on land. The behavior of fish in clean water aimed to move downstream at the beginning of the test and moving upstream in the end of the test. Fish exposition (12 days) under 0.05% urea and thiourea change their behavior in the water flow, which is expressed in the chaotic movement of fish relative to the current. Decreasing water level to the critical value (<3 cm) initiates climbing perch to crawling and moving on land. Two types of fish responses to decreasing water level were found: waiting, or crawling to land and moving. Based on the study diurnal locomotor activity, we found that the probability of climbing perch movements is higher in the daytime than in the dark.